OBSTACLES AND CHALLENGES IN THE CONSTRUCTION OF THE REGIONAL HOUSE OF REPRESENTATIVES BUILDING IN KUBU RAYA REGENCY - Nila Karmila; Verdico Arief (RADJA PUBLIKA, 2025)
This study examines the obstacles and challenges in the construction of the Kubu Raya Regency Regional People's Representative Council (DPRD) building, which has not yet been realized. This phenomenon is interesting to study because the Kubu Raya Regency DPRD has been renting a building since 2007, and construction is still planned until 2025. The method applied uses a qualitative approach, with data collection techniques including observation, interviews, and documentation studies. In this study, it refers to Bratakusumah's development planning theory as guidance, which includes five indicators of the success of a development project, namely the Presence of Assumptions Based on Facts, the Presence of Alternatives or Choices as the Basis for Determining Activities to be Carried Out, and the Presence of Goals to be Achieved, Predictive in nature as a step to anticipate possibilities that may affect the implementation of development, there is also a policy as the result of a decision that must be implemented. Research results indicate that the cause is the lack of commitment from the Regent of Kubu Raya Regency. In addition, another factor that affects it is the absence of a budget to realize the construction of the building.